1989
DOI: 10.1111/j.2042-7158.1989.tb06429.x
|View full text |Cite
|
Sign up to set email alerts
|

The transport of microspheres from the gastro-intestinal tract to inflammatory air pouches in the rat

Abstract: The distribution of latex microspheres (1.1 microns diam) has been investigated in-vivo, as a potential passive targeted system for the treatment of inflammation. Microspheres administered orally were found in the circulation and in inflamed tissues and exudates of inflammatory air pouches in rats. Oral absorption was also found in a rabbit. Particles administered directly into the circulation also penetrated into the air pouch tissues and fluids. The possibility of using microspheres as a passive targeted sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(22 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…This was roughly the same amount of time required for soluble dye tracers to cross the epithelium, indicating that the pathway has little resistance. Similar studies revealed that PLGA nanospheres were taken up in Peyer's patches after 1 h (Foster et al 1998) while uptake into the absorptive epithelium occurred within 30 min -1 h (Alpar et al 1990). …”
Section: Improving Uptake In the Gi Tractsupporting
confidence: 61%
“…This was roughly the same amount of time required for soluble dye tracers to cross the epithelium, indicating that the pathway has little resistance. Similar studies revealed that PLGA nanospheres were taken up in Peyer's patches after 1 h (Foster et al 1998) while uptake into the absorptive epithelium occurred within 30 min -1 h (Alpar et al 1990). …”
Section: Improving Uptake In the Gi Tractsupporting
confidence: 61%
“…Since, studies of PMNL phagocytosis of PNIPAm /MAA nanoparticles may provide information on the effects of serum factors on particle uptake, it was felt that HSA adsorption pro les may be more useful in assessing the effect of surface hydrophobicity on non-speci c particle uptake. We chose PMNLs and monocytes as model phagocytic cells, because the former is present in the blood whose phagocytic role is analogous to that of Kupffer cells in the liver [42], and the latter is able to derive to macrophages and often accumulate at in ammation sites such as rheumatoid arthritis [43].…”
Section: Introductionmentioning
confidence: 99%
“…oral delivery | uptake mechanism B eginning in the 1960s, several groups (1)(2)(3)(4)(5)(6)(7) demonstrated that the small intestine could absorb microparticles with a diameter >1 μm, challenging dogma that the small intestine could only absorb small macromolecules. After this discovery, researchers began engineering microspheres (MSs) to deliver drugs with poor water solubility (8)(9)(10), poor gastrointestinal permeability (11), or poor oral bioavailability (8,9,(12)(13)(14)(15) to the small intestine.…”
mentioning
confidence: 99%